HUBUNGAN KEHAMILAN GANDA, RIWAYAT ABORTUS, ANEMIA DENGAN KEJADIAN RETENSIO PLASENTA - Desmansyah, Desmansyah (JURNAL KESEHATAN TERAPAN, 2021)
According to the World Health Organization (WHO) data, it is reported that 15-20% of maternal deaths are due to retained placenta and its incidence is 0.8-1.2% for each birth. Compared to other risks of giving birth, postpartum hemorrhage where retained placenta is one of the causes can be life-threatening where mothers with heavy bleeding will quickly leave if they get proper medical care. Objective: to determine the relationship between multiple pregnancy, history of abortion, and anemia with the incidence of retained placenta. The design of this study is an analytic study with the approach method used "cross sectional". The population in this study were mothers who gave birth who experienced postpartum hemorrhage as many as 254 people and the sample in this study amounted to 156 people. Based on bivariate analysis with Chi-Square test showed that there was a relationship between multiple pregnancies value 0.001 < 0.05, there was no relationship with history of abortion value = 1,000 < 0.05, and there was a relationship between p value 0.003 < 0.05 with the incidence of retained placenta. . Suggestion: it is expected to be an input in making policies to improve health services, especially for the incidence of retained placenta Keywords: Gemelli, history of abortion, anemia, retained placenta